Racial and Ethnic Disparities in COVID‐19 Infections and Deaths Across U.S. Nursing Homes - Li, Yue (J Am Geriatr Soc, 2020)
BACKGROUND/OBJECTIVES: To determine racial/ethnic disparities in weekly counts of new COVID‐19 cases and deaths among nursing home residents or staff. DESIGN: Cross‐sectional analysis of national nursing home COVID‐19 reports linked to other data. Multivariable two‐part models modeled disparities in count of cases or deaths, and logistic regressions modeled disparities in self‐reported shortages in staff and personal protective equipment (PPE), across nursing home groups with varying proportions of racial/ethnic minority residents, defined as low‐, medium‐, medium‐high–, and high‐proportion groups. SETTING: A total of 12,576 nursing homes nationally. PARTICIPANTS: None. INTERVENTION: None. MEASUREMENTS: Numbers of incident COVID‐19 confirmed cases among residents and staff, and incident COVID‐19 related deaths among residents (primary outcomes); and nursing home reported shortages in staff and PPE (secondary outcomes). All outcomes were reported for the week of May 25, 2020. RESULTS: The number of weekly new COVID‐19 confirmed cases among residents ranged from an average of 0.4 cases per facility (standard deviation (SD) = 2.5) for the low‐proportion group (93.0% had zero new cases) to 1.5 cases per facility (SD = 6.3) for the high‐proportion group (78.9% had zero new cases). Multivariable regression estimated that compared with the low‐proportion group, the likelihood of having at least one new resident case was 76% higher (odds ratio = 1.76; 95% confidence interval = 1.38–2.25; P = .000) for the high‐proportion group. Similar across‐facility disparities were found for the weekly count of new COVID‐19 deaths among residents (ranging from 0.1 deaths per facility (SD = 1.1) for the low‐proportion group to 0.4 deaths (SD = 2.0) for the high‐proportion group) and in the weekly count of new COVID‐19 confirmed cases among staff (ranging from 0.3 cases (SD = 1.4] to 1.3 cases (SD = 4.4) per facility). No substantial disparities in self‐reported shortages of staff or PPE were found. CONCLUSION: Nursing homes caring for disproportionately more racial/ethnic minority residents reported more weekly new COVID‐19 confirmed cases and/or deaths. Immediate actions are needed to address these system‐level disparities.